Engineering of an Osteoinductive and Growth Factor‐Free Injectable Bone‐Like Microgel for Bone Regeneration (Adv. Healthcare Mater. 11/2023). Issue 11 (26th April 2023) - Subbiah, Ramesh; Lin, Edith Y.; Athirasala, Avathamsa; Romanowicz, Genevieve E.; Lin, Angela S. P.; Califano, Joseph V.; Guldberg, Robert E.; Bertassoni, Luiz E.
Abstract : Biomineralization Article 2200976 by Luiz E. Bertassoni and co‐workers presents injectable cell‐laden bone‐like tissue constructs that show promise as minimally invasive and growth factor‐free alternatives to bone autografts for repair and regeneration of critical sized bone defects. By approximating the cellular, structural, and chemical composition of native bone, the engineered microconstructs promote native‐like mechanisms of osteogenesis via unique mechanotransductive and phosphate signaling pathways.